(untitled) (REMUNOM, 2024)
This article aims to clarify the negative effect of the incorrect use of pesticides in Brazilian agriculture. Pesticides, which are chemical, physical or biological substances used especially in large crops, play a role in increasing agricultural productivity. However, bodies such as the World Health Organization (WHO) and the National Health Surveillance Agency (ANVISA) warn that the misuse of these products can cause significant damage to human well-being and the environment. Furthermore, the effects of these substances can be extremely harmful in the long term to the health of those exposed, and can result in various pathologies. The research is based on documents published between 2019 and 2024, addressing the inappropriate use of pesticides and its ramifications for human health and the environment.